BLE Beacon Plate 기법과 Pedestrian Dead Reckoning을 융합한 실내 측위 알고리즘 - 이지나(Ji-Na Lee); 강희용(Hee-Yong Kang); 신용태(Yongtae Shin); 김종배(Jong-Bae Kim) (한국정보통신학회논문지, 2018)
As the demand for indoor location recognition system has been rapidly increased in accordance with the increasing use of smart devices and the increasing use of augmented reality, indoor positioning systems(IPS) using BLE (Bluetooth Lower Energy) beacons and UWB (Ultra Wide Band) have been developed. In this paper, a positioning plate is generated by using trilateration technique based on BLE Beacon and using RSSI (Received Signal Strength Indicator). The resultant value is used to calculate the PDR-based coordinates using the positioning element of the Inertial Measurement Unit sensor, We propose a precise indoor positioning algorithm that combines RSSI and PDR technique. Based on the plate algorithm proposed in this paper, the experiment have done at large scale indoor sports arena and airport, and the results were successfully verified by 65% accuracy improvement with average 2.2m error. 스마트 기기의 생활화와 증강현실 활용 증가로 실내 위치 인식 시스템의 수요가 급증함에 따라, BLE(Bluetooth Lower Energy) 비콘 그리고 UWB(Ultra Wide Band) 등을 이용한 실내 측위 시스템이 개발되고 있다. 본 논문에서는 BLE Beacon을 기반으로 RSSI(Received Signal Strength Indicator)를 이용한 삼변측량(Trilateration) 기법을 사용하여 측위 플레이트(Plate)를 생성한다. 이에 IMU(Inertial Measurement Unit) 센서의 방향, 속도, 이동거리 등의 데이터를 이용하여 PDR(Pedestrian Dead Reckoning) 측위 좌표를 산출하여 정확도를 보정한다. 또, BLE 비콘(Beacon)의 RSSI를 적용한 플레이트(Plate) 기법과 PDR 기법이 융합된 정밀 실내 측위 알고리즘을 제안한다. 본 논문에서 제시한 알고리즘을 실제 대형 실내 경기장과 공항에 BLE 비콘을 설치, 실험하여 평균 2.2m 의 오차로 65%의 정확도가 개선됨을 검증하였다.